Neurological Complications in COVID-19 Patients: Can Analysis of Specific Antibodies and Viral RNA in Paired Cerebrospinal Fluid and Serum be Used for Accurate Diagnosis of SARS-CoV-2 Neuroinflammatory Disease? A Case Series - Karin Holst Lauridsen; Kristine Boisen Olsen; Eva Løbner Lund; Tomas O Jensen; Thomas Ingemann Pedersen; Zitta Barrella Harboe; Valeria Antsupova; Lasse Dam Rasmussen; Dennis Röser; Jytte Banner; Kristina Træholt Franck; Veronika Vorobieva Solholm Jensen (SAGE Publishing, 2022)
Background: Neurological complications during and after SARS-CoV-2 infection have been frequently described. The detection of either SARS-CoV-2 RNA or specific antibodies against SARS-CoV-2 in cerebrospinal fluid in the context of concomitant neurological manifestations indicates neuroinfection. Methods and Results: This is a retrospective descriptive analysis of cerebrospinal fluids and serum samples from 2 hospitalized patients and autopsy findings from 2 patients who died at home. Samples were analysed by 3 independent enzyme-linked immunosorbent assays. Specific antibodies against SARS-CoV-2 were detected in cerebrospinal fluids and paired serum in all 4 cases. Levels of antibodies in cerebrospinal fluids were highest in samples from a deceased man with critical progression of COVID-19 and detectable SARS-CoV-2 viral RNA in cerebrospinal fluid, serum, 4 brain biopsies and 15 additional tissue samples, though immunohistochemical staining for SARS-CoV-2 in brain tissue did not detect the virus. Conclusion: Detection of SARS-CoV-2 antibodies in paired serum and cerebrospinal fluid may support the presence of SARS-CoV-2 neuroinflammatory disease in patients with COVID-19 and neurological manifestations.